Influence of the COVID-19 lockdown on Spanish professional soccer teams` external demands according to their on-field ranking - Raya-González, J.; García-Calvo, T.; Rubio-Morales, A.; López del Campo, R.; Resta, R.; Ponce-Bordón, J. C. (Biology of Sport, 2022)
The main objective of this study was to analyse the changes in external demand parameters (e.g., total distance, high-speed running distance, accelerations/decelerations) in Spanish professional soccer teams after the COVID-19 lockdown considering their on-field ranking (i.e., teams whose ranking worsened after the COVID-19 lockdown [WRS] vs. teams that improved their ranking after the COVID-19 lockdown [IMP]). A total of 23,527 individual match observations were collected on players competing during the 2019/20 season in the First Spanish Professional soccer League (LaLiga). Goalkeepers and players who participated for less than 10 minutes in each match were excluded. Relative total distance (TD/min), distance covered at 21-24 km·h-1 (HIRD/min) and > 24 km·h-1 per minute (VHIRD/min), high metabolic load distance (HMLD), and the number of accelerations (3 m/s2 ) and decelerations (< 3 m/s2 ) performed were analysed by the ChryonHego video1tracking system. These variables were analysed during two differentiated periods, before the COVID-19 lockdown (i.e., 27 matches) and after the COVID-19 lockdown (i.e., 11 matches), and teams were classified into two groups according to their ranking (i.e., WRS vs. IMP). R-Studio was employed for data analysis and a mixed linear model was conducted. A decrease in external demands in all teams after the COVID-19 lockdown was observed, and this decrease was greater in WRS. These results suggest that, after an inactive period (i.e., the COVID-19 lockdown), teams that return with better physical performance, mainly related to high-intensity actions, have more possibilities of improving their final qualifying position.